Study on the Pasture Establishment Technique V. Effect of Reseeding of Natural Pastures with Cenchurus Ciliaris by Different Soil Working Methods and Fertilizer Treatments on Pasture Production - Cakravarty, A K; Verma, C M (Annals of Arid Zone, 2016)
An experiment wit h 4 methods of soil working. and seeding viz., (I) complete soil working; removal of weeds and seeding, (2) Harrowing, non removal of weeds and seeding (3) no soil working and seeding and (iv)n,g soil working and .no seeding was conducted in sandy soil of the Central Research Farm, Jodhpur. The plots were further fertilized with N,P, and NPK. fertilizers @ 22.4 kg each per hectare, keeping one of the subplots as control. Soil workings'~ and seeding was done in the first year only, but fertilizers were applied in different subplots consecutively for 3 years. Germination of seeds were comparatively higher in the plots where complete soil working and seeding was done, and herbage production from the pastures increased by 50, 18 and 37 per cent respectively in 3 successive years from the year of soil working and seeding. A Net profit of Rs. 103.55 per hectare was estimated for a period of 3 years. In all the three years nitrogen either singly or in combination with Phosphorus or Phosphorus and Potash indicated increase in height and tillering of plants as compared to those receiving no fertilizers But yield of herbage indicated increase in the first year only in similar set of treatments.